Molecularly imprinted polymers (MIP): From the bulk synthesis to hybrid material to classic and new applications - Pupin, Rafael R. [UNESP]; Monteiro, Gustavo C. [UNESP]; Foguel, Marcos V. [UNESP]; Bolzani, Vanderlan da S. [UNESP]; Pividori, Maria Isabel; Sotomayor, Maria del Pilar T. [UNESP] (My University, 2017)
Molecular imprinting has become one of the most effective techniques in developing biomimetic material and, within these approaches, molecularly imprinted polymers (MIP) have proven their potential in synthetic recognition. Their advantages, when compared to biological material (like enzymes and antibodies), include high chemical and thermal stability, easy preparation, low cost and proven stability in long-term storage. Additionally, MIP present many uses, from the preparation of samples, to Solid Phase Extraction (SPE), High Performance Liquid Chromatography (HPLC) and layer recognition in sensors. Therefore, because of the great potential of biomimetic polymers, this chapter will undertake the history of its development and synthesis methods, structural modifications that enable the formation of new MIP and its various uses. The scope of this chapter aims to highlight some of the examples of MIP synthesis and use, without covering the extensive literature available and providing a broad view of the field.
Keywords: Applications; Modification techniques; Molecularly imprinted polymers; Polymer synthesis